2021
DOI: 10.3390/su132413782
|View full text |Cite
|
Sign up to set email alerts
|

Robust Spatiotemporal Estimation of PM Concentrations Using Boosting-Based Ensemble Models

Abstract: Particulate matter (PM) as an air pollutant is harmful to the human body as well as to the ecosystem. It is crucial to understand the spatiotemporal PM distribution in order to effectively implement reduction methods. However, ground-based air quality monitoring sites are limited in providing reliable concentration values owing to their patchy distribution. Here, we aimed to predict daily PM10 concentrations using boosting algorithms such as gradient boosting machine (GBM), extreme gradient boost (XGB), and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The model with high accuracy is given higher weight to optimize the overall model. The ACC (Accuracy) weighted method is an alternative approach, akin to the MAE weighted method The ACC weighted method is learned from the SWE (Self-Weighted Ensemble) method [36] which is based on the F1-score to calculate the performance. The aim of the ACC weighted method is to reduce the weight of inaccurate learners and boost the reasonably-accurate weak learners so as to increase the recognition rate of the overall model.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The model with high accuracy is given higher weight to optimize the overall model. The ACC (Accuracy) weighted method is an alternative approach, akin to the MAE weighted method The ACC weighted method is learned from the SWE (Self-Weighted Ensemble) method [36] which is based on the F1-score to calculate the performance. The aim of the ACC weighted method is to reduce the weight of inaccurate learners and boost the reasonably-accurate weak learners so as to increase the recognition rate of the overall model.…”
Section: Background and Related Workmentioning
confidence: 99%
“…For example, once there are two features with 99% of correlation, decision tree will choose only one of them as statistic feature within the processes of deciding upon a split. Recently, the XGB method was used to address problems in atmospheric environment (Park et al 2021) and terrestrial ecosystems (Wang et al 2022b) and showed better potentials than traditional methods. Here, we apply the XGB model to reproduce site-level GPP based on eight climatic drivers including TA, diffuse radiation (SWdif), direct radiation (SWdir), VPD, CO 2 , WS, air pressure (P) and PRE.…”
Section: Extreme Gradient Boosting (Xgb) Modelmentioning
confidence: 99%
“…It incrementally constructs an ensemble by iteratively training a new model to emphasize misclassified training samples from previous models. Boosting helps reduce bias (underfitting) in classification problems [ 31 ].…”
Section: Introductionmentioning
confidence: 99%